Brand Trust Sebagai Mediasi User-Generated Content dan Influencer Marketing Terhadap Brand Equity Six Letters Coffee - Putu Viona Nita Putri; I Gusti Ngurah Oka Ariwangsa; Ida Bagus Raka Suardana; Ni Putu Nina Eka Lestari (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to analyze the brand trust in the relationship between user-generated content (UGC) and influencer marketing on brand equity at Six Letters Coffee, a local MSME located in Gianyar, Bali. The research is motivated by the limited digital engagement among MSMEs, particularly in optimizing authentic consumer content and influencer collaboration to strengthen brand value. Grounded in the Theory of Planned Behavior (TPB), this study examines how consumers’ attitudes and trust are shaped through digital interactions that influence brand perception. A quantitative approach was employed using purposive sampling, involving 160 respondents who actively engage with Six Letters Coffee’s social media content. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that UGC has a positive and significant effect on both brand trust and brand equity, while influencer marketing significantly affects brand equity but not brand trust. Moreover, brand trust exerts a significant mediating effect between UGC and brand equity, yet fails to mediate the relationship between influencer marketing and brand equity. These results emphasize that authentic consumer-generated content plays a more crucial role than influencer endorsement in fostering trust and strengthening brand equity. This research contributes to the development of digital marketing strategies for MSMEs, highlighting the importance of trust-based engagement in building sustainable brand value.